Enhancing Blood Collection Processes: A Phlebotomy Clinic Improvement Project - Joshua Wilkinson; Anna Sherratt; Eleanor Davies (BJPsych Open)
Aims: To determine whether an in-house phlebotomy clinic would reduce the length of time taken for blood tests to be completed and results reviewed within the CAMHS Eating Disorder Service in Coventry and Warwickshire Partnership NHS Trust, which would reduce patient safety incidents caused by these delays.